ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KARTU PRABAYAR XL DI SURAKARTA - Lorensa Agustin Betris N (KELOLA, 2018)
This research is titled “ANALYSIS OF FACTORS THAT INFLUENCE THE PURCHASE DECISION OF XL PREPAID CARDS IN SURAKARTA”. Aims to find out the significant variables of promotion, price, and brand image on the decision to buy prepaid XL cards in Surakarta. Those in five counters in five subdistricts in Surakarta. Sampling was taken by accident random sampling method. Data types and data sources are obtained from primary and secondary sources. Data was collected by making questionnaires regarding promotions, prices, and brand image. Data analysis tool : validity test, reliability test, classic assumption test, hypothesis testing consist of : multiple linear regression analysis, t test, F test and determination test. The results of multiple linear regression analysis show that the promotion and price variables affect the purchasing decision, while the brand image variable has a negative effect on purchasing decisions. The result of the t test indicate that the promotion and price variables have no significant effect on purchasing decisions, while the brand image variable has no significant effect on purchasing decisions. The result of the F test show that the promotion, price, and brand image variables influence together the purchase decision. The results of the coefficient of determination of the adjusted R square value obtained a result of 0,663 which means the decision to purchase prepaid cards XL can be explained by the promotion variable,  price, and brand image by 66,3 % while the remaining 33,7% is explained by other variables not included in the study.Keywords : promotion, price, brand image, and buying decision